Thermal ramping technique : a facile nanowires synthesis technique for gas sensing applications / Zainal Abidin bin Ali - Ali, Zainal Abidin (2012)
Nanowires of SnO2 have been successfully synthesized using a modified, simplified and less complicated carbothermal reduction technique, namely thermal ramping technique. This technique is developed to ease the synthesis process of nanowires for the development of gas sensing device. Contrary to conventional carbothermal reduction technique, no inert gas as a carrier is required. Distance of source material to substrates parameter is also eliminated. This new technique introduces ramping parameter to the conventional technique to compensate the elimination of the carrier gas. SnO2 was chosen as the raw material due to its wide availability, low-cost and widely used in the sensing devices. The SnO2 nanowires were synthesized under different controlled parameter such as heating temperature, Au catalyst and number of ramping. The morphological and crystal structure of the yielded nanowires were characterized using the field emission scanning electron microscopy (FESEM), Energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). It was discovered that nanowires density increased as the temperature increased. This could be attributed to the increased in the Sn, SnO, SnO2 and CO/CO2 vapour supply to the substrates. XRD results show that the nanowires yielded at 700 °C to 900 °C have tetragonal rutile structure of SnO2, whereas at 1000 °C, the nanowires yielded were detected to be SnO2, Sn3O4 and Sn2O3/SnO.SnO2. The density of SnO2 nanowires grown with Au catalyst was also observed to be significantly higher than that of SnO2 nanowires without Au catalyst. The SnO2 nanowires grown with and without Au catalyst can be attributed to the vapour-liquid-solid (VLS) and vapour-solid (VS) mechanism, respectively. Moreover, the density of the SnO2 nanowires also increased as the ramp number increased. No nanowires were observed in the first ramp. The SnO2 nanowires only started to appear in the second ramp and densified in the third ramp. In hydrogen gas sensing test, the iii sensor was observed to display the optimum performance at 200 °C, with response and recovery times were approximately 20 s and 140 s, respectively. At different hydrogen concentration, the sensitivities were observed to be highest and lowest at 1000 ppm and 200 ppm, respectively. The unstable and fluctuated electrical response and sensitivities of the sensor observed at 400 ppm, 300 ppm and 200 ppm could be attributed to the presence of water vapour on the sensor and complex reaction probably occurred between the vapour with the oxygen and hydrogen.